Multicomponent Lifestyle Interventions for Treating Overweight and Obesity in Children and Adolescents: A Systematic Review and Meta-Analyses - I. K. Ø. Elvsaas; L. Giske; B. Fure; L. K. Juvet (Hindawi Limited, 2017)
Background. Treatment of childhood obesity is important in preventing development of obesity-related diseases later in life. This systematic review evaluates the effect of multicomponent lifestyle interventions for children and adolescents from 2 to 18 years. Methods and Results. We performed systematic searches in nine databases. Thirty-nine studies met the criteria for meta-analyses. We found a significant difference in body mass index (BMI) after 6 months (MD −0.99 (95% CI −1.36 to −0.61)), 12 months (MD −0.67 (95% CI −1.01 to −0.32)), and 24 months (MD −0.96 (95% CI −1.63 to −0.29)) in favour of multicomponent lifestyle interventions compared to standard, minimal, and no treatment. We also found a significant difference in BMI Z scores after 6 months (MD −0.12 (95% CI −0.17 to −0.06)), 12 months (MD −0.16 (95% CI −0.21 to −0.11)), and 24 months (MD −0.16 (95% CI −0.21 to −0.10)) in favour of multicomponent lifestyle interventions. Subgroup analyses suggested an increased effect in specialist health care with a group treatment component included in the intervention. Conclusion. Multicomponent lifestyle interventions have a moderate effect on change in BMI and BMI Z score after 6, 12, and 24 months compared with standard, minimal, and no treatment.